2016
DOI: 10.1111/bjdp.12141
|View full text |Cite
|
Sign up to set email alerts
|

Greater number of group identifications is associated with healthier behaviour in adolescents

Abstract: We investigated the relationship between group identification (with the family, school, and friendship groups) and adolescent health behaviour (smoking, binge drinking, and cannabis use). 1,111 students from 4 Scottish secondary (high) schools completed a questionnaire which included measures of group identification, group contact, health behaviours, and demographic variables. We found that identification with the family and school groups predicted reduced odds of substance use, whereas identification with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 36 publications
3
18
0
Order By: Relevance
“…Another key limitation is that the present study does not explore variables that may mediate the relationship between T1 university identification and T2 SWL. Social identity researchers have explored a number of possible processes through which group identification may impact upon well‐being, such as identification enhancing perceived personal control (Greenaway et al., ), satisfying core psychological needs (Greenaway, Cruwys, Haslam, & Jetten, ), encouraging one to believe that useful social support will be available during stressful life events (Haslam, Jetten, Postmes, & Haslam, ), and encouraging one to behave more healthily (Miller, Wakefield, & Sani, ; Sani et al., ). These processes are unlikely to be mutually exclusive, and future work should do more to explore the extent to which these (and other) processes mediate the link between group identification and SWL.…”
Section: Discussionmentioning
confidence: 99%
“…Another key limitation is that the present study does not explore variables that may mediate the relationship between T1 university identification and T2 SWL. Social identity researchers have explored a number of possible processes through which group identification may impact upon well‐being, such as identification enhancing perceived personal control (Greenaway et al., ), satisfying core psychological needs (Greenaway, Cruwys, Haslam, & Jetten, ), encouraging one to believe that useful social support will be available during stressful life events (Haslam, Jetten, Postmes, & Haslam, ), and encouraging one to behave more healthily (Miller, Wakefield, & Sani, ; Sani et al., ). These processes are unlikely to be mutually exclusive, and future work should do more to explore the extent to which these (and other) processes mediate the link between group identification and SWL.…”
Section: Discussionmentioning
confidence: 99%
“…Each item was rated on a 1-7 scale (higher values = stronger identification), and the overall mean was found for each group. In accordance with validation studies, a participant was considered to identify with a particular social group if they scored 5 or more for that group (34,43). We then counted the number of groups with which the participant identified (ranging between 0 and 3; M = 2.18, SD = .90).…”
Section: Methodsmentioning
confidence: 99%
“…Much of this research has focused on social group connectedness, in the form of subjective self-definition in terms of particular group memberships (e.g., a teacher, a member of the church, a metalhead). Studies have suggested that group memberships not only protect against a decline in mental health (32), but that they are also associated with fewer health risk behaviours such as smoking (33,34). The benefits of social group membership for health have been shown to also be strong among vulnerable communities, such as people experiencing homelessness (35) and people recovering from trauma (36).…”
Section: Social Isolation and Frequent Attendancementioning
confidence: 99%
“…We created three binary variables to allow us to sum the number of high group identifications participants had (for further examples of this method see Miller et al, 2015Miller et al, , 2016aSani et al, 2015a,b). One variable was created for each group identification measure; family (T 1 : M = 0.85, SD = 0.36; T 2 : M = 0.79, SD = 0.40), school (T 1 : M = 0.59, SD = 0.49; T 2 : M = 0.54, SD = 0.50), and friendship group (T 1 : M = 0.82, SD = 0.38; T 2 : M = 0.81, SD = 0.40).…”
Section: Questionnaire Measures Group Identificationmentioning
confidence: 99%